2021
DOI: 10.1177/13591053211024724
|View full text |Cite
|
Sign up to set email alerts
|

Psychology’s medicalization of male baldness

Abstract: Male baldness is physically benign though it is increasingly described as a “disease” based on claims that it is profoundly distressing. The medicalization of baldness was assessed using data extracted from a review of 37 male baldness psychosocial impact studies. Findings revealed most studies likely had commercial influences (78%), represented baldness as a disease (77%), were conducted on biased samples (68%), and advocated for baldness products/services (60%), omitting their limitations (68%). Health psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…For example, participants estimated 25% of AGA research was commercially biased when evidence has found at least 66% is. 4,5 Commercial influences abound in the AGA 'information landscape' generally.…”
Section: Aga' Commercial Influences Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…For example, participants estimated 25% of AGA research was commercially biased when evidence has found at least 66% is. 4,5 Commercial influences abound in the AGA 'information landscape' generally.…”
Section: Aga' Commercial Influences Summarymentioning
confidence: 99%
“…Practitioner roles are further challenged by the widespread presence of AGA commercial influences. Approximately 70% of popular hair loss Facebook pages are funded, written or influenced by businesses 3 as is more than 60% of hair loss research 4,5 . For example, Alfonso et al 6 conducted an international study on the psychosocial impact of AGA published in the journal Current Medical Research and Opinion (hereafter referred to as the Alfonso study).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many concerns previously perceived as normal human differences or problems have now been defined as tractable illnesses that can benefit from diagnosis and often lifetime drug taking (Conrad 1992, Deyo and Patrick 2005, Moynihan and Cassells 2005. These include shyness and sadness (Horwitz andWakefield 2007, Lane 2007), tallness in girls (Rayner, Pyett et al 2010), baldness in men (Jankowski and Frith 2021) and many, many more normal human differences and phases of life. Le Fanu has described galloping medicalisation as an iatrogenic catastrophe (Le Fanu 2018).…”
Section: The Medicalisation and Commodification Of Cessationmentioning
confidence: 99%
“…Much prior, often pharmaceutically sponsored, research investigated the detrimental effects of MPBits onset, duration, degree, etc.on subjective well-being and the distress-reducing effects of MPB treatment (for an overview, see Frith & Jankowski, 2023). An entire industry thrives on selling anti-MPB drugs and thus has a strong interest in proving not only the dermatological but also the psychological effectiveness of MPB treatment (Jankowski & Frith, 2022). There has been limited research, however, on psychological factors underlying men's baldness distress.…”
mentioning
confidence: 99%